2003
DOI: 10.1007/s00253-002-1172-8
|View full text |Cite
|
Sign up to set email alerts
|

Sterols in microorganisms

Abstract: Sterols are vital components of all eukaryotic cells. This review describes the variety of sterol structures found in microalgae, yeasts, fungi, protozoans and microheterotrophs. Reports of the occurrence of sterols in prokaryotic cells are critically assessed. Methylotrophic bacteria contain unusual 4-methylsterols, but reports of 4-desmethyl sterols in cyanobacteria and other bacteria are limited and many of these seem dubious. Possible application areas for sterols derived from mass culture of microalgae an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
478
2
12

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 726 publications
(522 citation statements)
references
References 147 publications
14
478
2
12
Order By: Relevance
“…For all sediment samples, campesterol had minor amount with only constituted 1-4% of the total measured sterols. Brassicasterol was reported to be a more useful specific biomarker for some diatoms (Volkman, 2003;Hernandez et al, 2008). High concentrations of brassicasterol in sites from coastal areas support that the sediments in the coastal areas of Jiangsu Provinces and Shandong Provinces received more diatoms input (Table 1), which was in agreement with the observation from Di et al (2013) and Liu et al (2009).…”
Section: Sterolssupporting
confidence: 83%
See 2 more Smart Citations
“…For all sediment samples, campesterol had minor amount with only constituted 1-4% of the total measured sterols. Brassicasterol was reported to be a more useful specific biomarker for some diatoms (Volkman, 2003;Hernandez et al, 2008). High concentrations of brassicasterol in sites from coastal areas support that the sediments in the coastal areas of Jiangsu Provinces and Shandong Provinces received more diatoms input (Table 1), which was in agreement with the observation from Di et al (2013) and Liu et al (2009).…”
Section: Sterolssupporting
confidence: 83%
“…However, Volkman (2003) and more recently Rampen et al (2009) showed that these compounds are also present in several groups of microalgae. Sitosterol was more abundant than stigmasterol, 125 ± 58 ng/g and 25 ± 13 ng/g, respectively in this study.…”
Section: Sterolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tricyclic compounds originated from algae and bacteria during the Ordovician (Moldowan et al, 1983;Ourisson et al, 1982;Zumberge, 1987). The relative abundance of regular steranes can be used as a biomarker indicator of contributing organisms and it has been suggested that the C 27 sterane is sourced from marine planktons while the C 29 sterane is derived from land plants (Huang and Meinschein, 1979;Volkman, 1986) or from microalgae (Volkman, 2003). As would be expected the ternary plot of steranes in the Ordovician samples reveals an abundance of C 27 steranes (Fig.…”
Section: Origin Of Organic Mattersupporting
confidence: 54%
“…Yet, the most common D 5,7 -sterols (precursors of D 3,5,7 -steratrienes) possess 28 carbon atoms. Thus, ergosterol, a major C 28 D 5,7 -sterol common in most protozoa and fungi, is the most widespread D 5,7 -sterol (Nes and McKean, 1977;Patterson, 1994;Volkman, 2003; and references cited therein). As a result, sedimentary MAs and MBs will be enriched in C 28 members compared to other steroidal biomarkers.…”
Section: Precursors Of Mas and Mbs In Sedimentsmentioning
confidence: 99%